Hepatocellular cancer pain: impact and management challenges - Christian-Miller N (Journal of Hepatocellular Carcinoma, 2018)
Nathaniel Christian-Miller,1 Catherine Frenette2 1Scripps Clinical Research, Scripps, San Diego, CA, USA; 2Scripps Center for Organ and Cell Transplantation, Scripps Green Hospital, La Jolla, CA, USA Abstract: Hepatocellular carcinoma (HCC) remains the most common primary liver malignancy. Pain comprises one of the most pervasive and troubling symptoms of HCC and may have severely negative effects on patient’s quality of life. Furthermore, because HCC frequently arises in the setting of cirrhosis, treating pain related to this malignancy poses a clinical challenge. This article summarizes manifestations of hepatocellular cancer pain, common obstacles to treatment, and practical HCC pain management. Keywords: hepatocellular carcinoma, health-related QOL, analgesic, opioid, loco-regional therapy, cirrhosis